Creation of the first national linked colorectal cancer dataset in Scotland: prospects for future research and a reflection on lessons learned : Creation of Scottish colorectal cancer dataset for research purposes - Hanna, Catherine; Lemmon, Elizabeth; Ennis, Holly; Jones, Robert; Hay, Joy; Halliday, Roger; Clark, Steve; Morris, Eva; Peter, Hall (International Journal of Population Data Science, 2021)
Introduction Current understanding of cancer patients, their treatment pathways and outcomes relies mainly on information from clinical trials and prospective research studies representing a selected sub-set of the patient population. Whole-population analysis is necessary if we are to assess the true impact of new interventions or policy in a real-world setting. Accurate measurement of geographic variation in healthcare use and outcomes also relies on population-level data. Routine access to such data offers efficiency in research resource allocation and a basis for policy that addresses inequalities in care provision. Objective Acknowledging these benefits, the objective of this project was to create a population level dataset in Scotland of patients with a diagnosis of colorectal cancer (CRC). Methods This paper describes the process of creating a novel, national dataset in Scotland. Results In total, thirty two separate healthcare administrative datasets have been linked to provide a comprehensive resource to investigate the management pathways and outcomes for patients with CRC in Scotland, as well as the costs of providing CRC treatment. This is the first time that chemotherapy prescribing and national audit datasets have been linked with the Scottish Cancer Registry on a national scale. Conclusions We describe how the acquired dataset can be used as a research resource and reflect on the data access challenges relating to its creation. Lessons learned from this process and the policy implications for future studies using administrative cancer data are highlighted.